An agent based Keynesian model with credit cycles and countercyclical capital buffer - Zsuzsanna Hosszú; Bence Mérîo (Magyar Nemzeti Bank, 2017)
In this paper, we have developed an agent-based Keynesian macro model that features a detailed representation of a banking system, besides households and firms, and in which fiscal, monetary and macroprudential policy regulators also operate. The banking system generates longer credit cycles on the time series compared to the business cycle, and also fosters growth through lending, but deepens the recession during crises by decreasing credit supply. Macroprudential authority uses countercyclical capital buffer requirements to decrease the procyclicality of the banking system. According to our results, this policy instrument is effective in enhancing financial stability, while in recessions, the decrease in GDP is less with countercyclical capital buffer requirements than without any macroprudential rule. However, there is a trade-off between financial stability and economic growth.
Keywords: E12; E32; E44; G18; G21; 330; agent based model; credit cycle; business cycle; countercyclical capital buffer